Relationship between sex hormones and migraine - AlGawwam, Gheyath (Journal of the Faculty of Medicine Baghdad, 2015)
Back ground: Migraine is a common chronic episodic disabling primary headache disorder with associated Symptoms. The neuroendocrinological alterations, disorders of the hypothalamic-hypophysial axis are believed to be implicated in the pathogenesis of primary headache syndromesObjective: The aim is to determine the effect of sex hormones on migraine.Patients and methods: Twenty seven adult patients with migraine and 20 controls were assessed for prolactin,testeron,,LH,FSH were tested with immunofluorometric assay.Results: This study found that migraine is associated with elevated level of FSH, prolactin and testerone P= (